Transient Stability Augmentation of the Algerian South-Eastern Power System including PV Systems and STATCOM - Bouhadouza, B.; Bouktir, T.; Bourenane, A. (Engineering, Technology & Applied Science Research, 2020)
The transient stability of the 12-bus Algerian southeast power system is studied in this paper. This electrical system has abundant reactive power due to the long transmission lines and generators’ voltage. This capacitive power increases bus voltage which leads to network instability. The use of conventional compensators does not provide adequate and fast solutions. FACTS technology improves the efficiency of these compensators in solving the problem of power system instability efficiently. Among its elements, a synchronous compensator STATCOM control is proposed to decrease bus overvoltage and damping oscillations. Disturbance at bus B-1 is taken into consideration. This disturbance represents the photovoltaic (PV) array which exploits the abundantly available solar irradiation in the desert of Algeria. Various simulation tests have been carried out using NEPLAN software and the proposed design algorithms are proved in the relevant discussion.